Basal medium eagle solution may improve the post-thaw parameters of kangal dog semen - Sukru Gungor; Mustafa Numan Bucak (Eurasian Journal of Veterinary Sciences)
Aim: The aim of this study was to investigate the effects of BME on Kangal dog sperm parameters following the freezethawing process. Materials and Methods: Ejaculates were collected by digital manipulation twice a week. Ejaculates divided into six equal aliquots, and diluted with Tris-based extender (T) containing 5% glycerol (G) + BME 2.5% (TGB2.5), TG + BME 10% (TGB10), 5% ethylene glycol (E) + BME 2.5% (TEB2.5), TE + BME 10% (TEB10), TG and TE. Subsequently, the ejaculates were cooled to 4°C at 1.5 hours, and stored in liquid nitrogen (~-196°C). Results: The extender supplemented with 10% BME + 5% G resulted in higher progressive motility (23.19%), in comparison to the extenders supplemented with 5% EG (14.08%). Better sperm acrosome integrity was achieved with the use of the extender containing 2.5% BME + 5% G (44.99%), when compared to the use of the extender supplemented with 5% G (33.63%) (P<0.05). Conclusion: BME added to extender, may improve the postthawed sperm parameters on freezing of Kangal dog semen.